Influence of climatic drivers and long term N fertilization on the production and leaching of dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) in a Norway spruce (Picea abies) forest stand - Rappe George, Martin (2010)
The influence of long-term nitrogen (N) fertilization and climatic drivers on the production and leaching of dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) was studied in a Norway spruce (Picea abies (L.) Karst.) forest stand. DOC and DON soil solution concentrations in the O horizon were roughly an order of magnitude larger than B horizon soil solution concentrations. Soil solution sampled in the O horizon did not seem to respond to N fertilization. In the B horizon, however, slightly elevated concentrations of DOC and DON were occasionally observed in the fertilized plots. There did not seem to be a substantial effect of N fertilization on soil solution concentrations of DOC and DON. A decisive influence of simple climatic drivers on the within-year dynamics of DOC and DON soil solution concentrations could not be determined in this work. The annual mean DOC concentrations were higher 2009 than 1995, which might reflect an influence of the tree stand development on DOC soil solution concentrations.